MOLECULAR FRACTIONATION WITH CONJUGATE CAPS STUDY OF THE INTERACTION OF THE ANACARDIC ACID WITH THE ACTIVE SITE OF TRYPANOSOMA CRUZI GAPDH ENZYME: A QUANTUM INVESTIGATION - MÁRCIA MACHADO MARINHO; RICARDO PIRES DOS SANTOS; EVELINE MATIAS BEZERRA; RONER FERREIRA COSTA; CIRO SIQUEIRA FIGUEIRA; ALICE MARIA COSTA MARTINS; PEDRO LIMA NETO; EMMANUEL SILVA MARINHO; VALDER NOGUEIRA FREIRE; EUDENILSON LINS ALBUQUERQUE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to use the molecular fractionation with conjugate caps (MFCC) method to elucidate the possible interaction mechanism of anacardic acid (AA) with the saturated alkyl chain (AA0) in the Trypanosoma cruzi glyceraldehyde-3-phosphate dehydrogenase (TcGAPHD) enzyme. Methods: Initially, the geometry optimization of the AA three-dimensional structure (with the pentadecyl chain) was performed using density functional theory (B3LYP) calculations. With the AA0 optimization data, it was possible to plot the molecular electrostatic potential (MESP) surface. Molecular docking simulation was performed using automated coupling with the AutoDock Vina program. The best-fit conformation in the docking simulation of AA0 is the binding site used for the construction of the TcGAPHD-AA0 complex. Interaction energies between the AA0 molecule and the amino acid residues of the TcGAPHD enzyme were estimated using the MFCC strategy. Results: To obtain more reliable quantitative information on the interaction of AA with the active site of the TcGAPHD enzyme, the fragmentation method was combined with conjugated layers (MFCC) and molecular docking. It can be observed that the AA0 molecule occupies a region near the active site of the chalepin molecule in the TcGAPHD enzyme, and the Ile13 residue has the strongest binding energy of approximately 25 kcal/mol with AA0, through a strong Van der Waals interaction. Conclusion: The paper presents an improved quantitative analysis approach for assessing the contribution of individual amino acids to the free energy of interaction between AA and TcGAPHD. Specifically, the paper illustrates the advantageous approach of combining molecular docking with the MFCC method.